Low-temperature compact high-entropy alloy and preparation method thereof

By adjusting the molar ratio of Ti, Zr, Ta, Ni and the ball mill vacuum sintering process, the problem of high melting point of high entropy alloys is solved, and the preparation of low-temperature dense high entropy alloys is achieved, which improves the preparation efficiency and performance, and is suitable for structural damage integration. Material.

CN119121025APending Publication Date: 2024-12-13CHINA WEAPON SCI ACADEMY NINGBO BRANCH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411098706.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The high melting point of existing high entropy alloys makes it difficult to prepare, and prone to segregation and casting defects, limiting the preparation and application of large-sized components.

Method used

By adjusting the molar ratios of Ti, Zr, Ta and Ni to 1:1:1:0.2~0.8, ball milling and vacuum sintering processes are used to reduce the melting point of the alloy, and the tissue controllable through pressureless sintering of 1100~1300°C Forming and preparation.

Benefits of technology

The preparation of low-temperature dense high-entropy alloy is realized, retaining the alloy's strength and anti-detonation loading capacity, while reducing plasticity, improving the crushing efficiency after high-speed impact, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121025A_ABST
    Figure CN119121025A_ABST
Patent Text Reader

Abstract

The low-temperature compact high-entropy alloy is characterized in that the molar ratio of Ti to Zr to Ta to Ni in the alloy is 1: 1: 1: (0.2-0.8). The preparation method of the high-entropy alloy comprises the following steps: (1) weighing Ti, Zr, Ta and Ni raw material powder according to a designed ratio, and uniformly mixing in a ball milling tank; (2) filling the uniformly mixed TiZrTaNix powder into a crucible, and compacting by vibration; and (3) carrying out vacuum sintering on the compacted TiZrTaNix mixed powder, and carrying out furnace cooling to obtain the low-temperature compact high-entropy alloy. The melting point of the alloy is greatly reduced through low-temperature eutectic reaction of the introduced component Ni, Ti and Zr, so that the sintering densification temperature of the alloy is reduced to 1300 DEG C or below.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an alloy material, in particular to a high entropy alloy, and also to a preparation method of the alloy, belonging to the technical field of alloys. Background Art

[0002] In recent years, the application potential of high-entropy alloys in structural damage-integrated materials has attracted widespread attention in the field of weapons. First, high-entropy alloys have a "high entropy effect" in thermodynamics, are easy to form strongly distorted solid solution structures, and have high intrinsic strength; second, high-entropy alloys have a "topologically ordered structure", which provides the possibility for dislocation formation and activation, has a certain plastic deformation ability, and has strong resistance to detonation loading; third, the constituent elements of high-entropy alloys are mostly refractory elements with high combustion calorific values ​​and high energy density. In theory, high-entropy alloys with high strength, high energy density and certain plasticity can be used as structural damage-integrated materials, providing kinetic energy armor-piercing capabilities while bringing about damage aftereffects such as combustion arson, high temperature and overpressure, effectively enhancing the damage power of the warhead. The National University of Defense Technology has developed HfZrTiTa x The system's gun firing experiment confirmed for the first time that high-entropy alloys have the characteristics of combustion and energy release under high-speed impact loads. The concept of energetic high entropy was born and became a new research hotspot in the field of high entropy.

[0003] However, the existing energetic high entropy system is usually composed of refractory elements, and the overall melting point of the alloy is relatively high (≥1700℃), which exceeds the limit working conditions of most powder metallurgy equipment. Therefore, energetic high entropy alloys are mainly prepared by melting and casting processes. However, due to the large difference in melting points between high entropy alloy components and a wide liquid-solid two-phase region, the alloy is prone to component segregation during the melting and cooling process, and casting defects such as shrinkage and shrinkage holes are generated. The technical bottleneck of the preparation of large-size components has greatly restricted the promotion and application of high entropy alloys. Under this technical background, it is of great significance to develop an energetic high entropy alloy system with low-temperature compactness and combine it with powder metallurgy technology to realize the preparation and forming of high entropy alloy components, which is of great significance to promote the development and application of energetic high entropy alloys. Summary of the invention

[0004] The first technical problem to be solved by the present invention is to provide a low-temperature dense high-entropy alloy that can significantly reduce the melting point of the alloy in response to the above-mentioned technical status quo.

[0005] The second technical problem to be solved by the present invention is to provide a method for preparing a low-temperature dense high-entropy alloy that can significantly reduce the melting point of the alloy in response to the above-mentioned technical status quo.

[0006] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: a low-temperature dense high-entropy alloy, characterized in that the molar ratio of the components Ti, Zr, Ta and Ni in the alloy is 1:1:1:0.2-0.8.

[0007] The technical solution adopted by the present invention to solve the above second technical problem is: a method for preparing a low-temperature dense high-entropy alloy, characterized by comprising the following steps:

[0008] ① Weigh Ti, Zr, Ta and Ni raw material powders according to the designed ratio and mix them evenly in a ball mill;

[0009] ② Mix the uniform TiZrTaNi x The powder is filled into the crucible and compacted;

[0010] ③ The compacted TiZrTaNi x The mixed powder is vacuum sintered and cooled in the furnace to obtain a low-temperature dense high-entropy alloy.

[0011] Preferably, in step ①, the particle size of the Ti powder is 10-60 μm; and the purity of the Ti powder is ≥99.95%.

[0012] Preferably, in step ①, the particle size of the Zr powder is 45-74 μm; the purity of the Zr powder is ≥99.95%.

[0013] Preferably, in step ①, the particle size of the Ta powder is 30-50 μm; the purity of the Ta powder is ≥99.95%.

[0014] Preferably, in step ①, the particle size of the Ni powder is 2.5-10 μm; and the purity of the Ni powder is ≥99.95%.

[0015] Preferably, the ball milling conditions in step ① are as follows: rotation speed 80-150 rpm, ball-to-material ratio 1:2-2:1, ball milling time 4-6 h, and inert atmosphere protection.

[0016] Preferably, the vacuum sintering process parameters in step ③ are: sintering temperature 1100-1300° C., holding time 2-3 h, vacuum degree ≤10 Pa.

[0017] Compared with the prior art, the advantages of the present invention are: the low-temperature dense TiZrTaNi x High entropy alloy, the element Ni is introduced into TiZrTa alloy, and the melting point of the refractory high entropy alloy is greatly reduced through the low-temperature eutectic reaction of Ni with Ti and Zr components. The molding and preparation of alloy components with controllable structure can be achieved through pressureless sintering at 1100-1300°C. The high entropy alloy of the present invention reduces the plasticity of the alloy while retaining the alloy strength and anti-detonation loading ability, improves the crushing efficiency of the alloy after high-speed impact, and helps to improve the impact energy release characteristics of the high entropy alloy. At the same time, by adjusting the content of the component Ni, TiZrTaNi x Matching the strength and toughness of high entropy alloys to cope with different service scenarios.

[0018] Preparation method of high entropy alloy of the present invention, TiZrTaNi x The mixed powder does not need to be cold pressed into a green compact, but can be sintered after vibration, thus avoiding the delamination and cracking of the green compact during the cold pressing and demoulding process. The alloying reaction and densification of the components can be achieved through vacuum sintering at 1100-1300℃. The process is simple, the equipment requirements are low, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Example 1 low temperature dense TiZrTaNi 0.2 X-ray diffraction pattern of high entropy alloy.

[0020] Figure 2 Example 1 low temperature dense TiZrTaNi 0.2 SEM image of high entropy alloy.

[0021] Figure 3 Example 1 low temperature dense TiZrTaNi 0.2 Quasi-static compressive stress-strain curves of high-entropy alloys.

[0022] Figure 4 Example 1 low temperature dense TiZrTaNi 0.2 Photo of the test of the ignition effect of high entropy alloy on the quilt after it penetrated the target plate at 800m / s.

[0023] Figure 5 This is the SEM image of the comparative TiZrTa high entropy alloy.

[0024] Figure 6 This is the X-ray diffraction pattern of the comparative induction melted TiZrTa high entropy alloy.

[0025] Figure 7 This is the SEM image of comparative induction melted TiZrTa high entropy alloy.

[0026] Figure 8 Quasi-static compressive stress-strain curve of comparative induction melted TiZrTa high entropy alloy.

[0027] Fig. 9 This is a test photo of the ignition effect of the comparative induction-melted TiZrTa high-entropy alloy on the quilt after it penetrated the target plate at 800m / s.

[0028] Fig.10 The low temperature dense TiZrTaNi obtained in Example 2 0.4 SEM image of high entropy alloy.

[0029] Fig.11 The low temperature dense TiZrTaNi obtained in Example 30.6 SEM image of high entropy alloy.

[0030] Fig.12 The low temperature dense TiZrTaNi obtained in Example 4 0.8 SEM image of high entropy alloy. DETAILED DESCRIPTION

[0031] The following is a further explanation of the present invention, but not a limitation of the present invention. The described embodiments are only a part of the embodiments of the present invention, but not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In the following embodiments:

[0033] The purity of metal elements Ti, Zr, Ta, and Ni is greater than 99.9%, the particle size of Ti powder is 10-60μm, the particle size of Zr powder is 45-74μm, the particle size of Ta powder is 30-50μm, and the particle size of Ni powder is 2.5-10μm. First, a uniform TiZrTaNi x The powders were mixed, ball milled at a speed of 80 to 150 rpm, a ball-to-material ratio of 1:2 to 2:1, and the ball milling time was 4 to 6 hours; then, the powders were filled into a crucible and compacted; finally, TiZrTaNi was obtained by vacuum sintering. x The mixed powder is compactly formed, the sintering temperature is 1100-1300°C, the insulation time is 2-3h, and the vacuum degree is ≤10Pa.

[0034] Example 1

[0035] S1: Weigh 144.2 g of Ti powder, 275.0 g of Zr powder, 545.4 g of Ta powder, and 35.4 g of Ni powder in a molar ratio of 1:1:1:0.2, and place them in a ball mill;

[0036] S2: Add 500g of stainless steel grinding balls according to the ratio of the mass of grinding balls to the total mass of raw material powder (including Ti powder, Zr powder, Ta powder, Ni powder) of 1:2;

[0037] S3: Ball milling for 4 h under inert atmosphere at a speed of 120 rpm to obtain uniform TiZrTaNi 0.2 Mixing powders;

[0038] S4: TiZrTaNi 0.2 The mixed powder is filled into an alumina crucible and vibrated, and then placed in a vacuum sintering furnace for compacting. The sintering temperature is 1300°C, the holding time is 2h, and the low-temperature dense TiZrTaNi is obtained after the furnace is cooled. 0.2 High entropy alloys;

[0039] The low temperature dense TiZrTaNi obtained in Example 1 0.2 The high entropy alloy was subjected to SEM testing, X-ray diffraction, quasi-static compression, and gun-fired ignition quilt testing. The results are as follows:

[0040] Figure 1 The low temperature dense TiZrTaNi obtained in Example 1 0.2 SEM image of high entropy alloy. There is no obvious hole defect in the alloy cross section, which proves that vacuum sintering at 1300℃ can achieve TiZrTaNi 0.2 Densification of high entropy alloys. TiZrTaNi 0.2 High entropy alloys are mainly composed of two contrasting phases, namely a light-colored Ta-rich phase and a dark-colored Ni-rich phase.

[0041] Figure 2 The low temperature dense TiZrTaNi obtained in Example 1 0.2 X-ray diffraction pattern of high entropy alloy. According to the spectrum, the main phase of the alloy is BCC phase, and there are also diffraction peaks of some Ti(Zr)-Ni intermetallic compounds.

[0042] Figure 3 The low temperature dense TiZrTaNi obtained in Example 1 0.2 The quasi-static compressive stress-strain curve of the high-entropy alloy shows that the alloy yield strength is 1286MPa. After reaching the elastic deformation limit, plastic deformation continues to occur. The final quasi-static compressive strength reaches 1534MPa, and the fracture strain is 8.7%, which can meet the application requirements of structural damage integrated materials.

[0043] Figure 4 The low temperature dense TiZrTaNi obtained in Example 1 0.2 Photo of the test of the ignition effect of high entropy alloy on the quilt behind the target. 0.2 The high-entropy alloy can effectively penetrate the 6mm thick front steel plate at a speed of 800m / s, then break into a cloud of small fragments and undergo a violent combustion reaction, successfully igniting the quilt behind the target with obvious flames, showing excellent impact response characteristics.

[0044] Comparative Example 1

[0045] S1: Weigh 149.6 g Ti powder, 285.0 g Zr powder, and 565.4 g Ta powder in a molar ratio of 1:1:1, and place them in a ball mill;

[0046] S2: Add 500g of stainless steel grinding balls according to the ratio of the mass of grinding balls to the total mass of raw material powder (including Ti powder, Zr powder, Ta powder) of 1:2;

[0047] S3: ball milling for 4 h under inert atmosphere protection at a ball milling speed of 120 rpm to obtain a uniform TiZrTa mixed powder;

[0048] S4: The TiZrTa mixed powder is filled into an alumina crucible and compacted, and then placed in a vacuum sintering furnace for compaction. The sintering temperature is 1300°C, and the holding time is 2h. After the furnace is cooled, a TiZrTa alloy block is obtained.

[0049] S5: Put the TiZrTa alloy block into a melting crucible and melt it using a high-frequency induction melting device with a heating power of 24 kW and a melting time of 2 min. Cool the furnace to room temperature to obtain a TiZrTa high entropy alloy.

[0050] The TiZrTa high entropy alloy prepared by sintering at 1300°C obtained in Comparative Example 1 was observed by SEM, and the results are as follows:

[0051] Figure 5 This is the SEM image of the TiZrTa high entropy alloy prepared by sintering at 1300°C in Comparative Example 1. It can be found that there are still a large number of hole defects in the alloy cross section and it is not completely dense.

[0052] The TiZrTa high entropy alloy prepared by melting in Comparative Example 1 was subjected to SEM observation, X-ray diffraction, quasi-static compression and gun-fired ignition quilt test, and the results are as follows:

[0053] Figure 6 This is a SEM image of the TiZrTa high entropy alloy prepared by induction melting in Comparative Example 1. After secondary melting, the alloy is completely dense and the contrast is basically uniform, indicating that the alloy may have a single-phase structure.

[0054] Figure 7 This is the X-ray diffraction pattern of the TiZrTa high entropy alloy prepared by induction melting in Comparative Example 1. The spectrum shows that the alloy has only one set of BCC diffraction peaks, confirming that the TiZrTa high entropy alloy prepared by melting has a single-phase BCC structure, which is consistent with the SEM detection results.

[0055] Figure 8 The quasi-static compressive stress-strain curve of the TiZrTa high entropy alloy prepared by induction melting in Comparative Example 1 shows that the alloy has a yield strength of 1305 MPa. After reaching the elastic deformation limit, it continues to undergo large plastic deformation, and the final quasi-static compressive strength reaches 1529 MPa, with a fracture strain of 18.2%. For the special service scenario of structural damage integrated materials, excessive plasticity is not conducive to crushing energy release under dynamic impact loads.

[0056] Fig. 9This is a test photo of the ignition effect of the TiZrTa medium entropy alloy prepared by induction melting on the target back quilt at 800m / s in Comparative Example 1. The TiZrTa high entropy alloy can effectively penetrate the 6mm thick front steel plate at a speed of 800m / s, then break into a cloud of fragments and undergo a combustion reaction, but due to the excessive plasticity of the alloy, the crushing is insufficient, and the combustion flame is significantly weaker than that of the TiZrTaNi obtained in Example 1. 0.2 High entropy alloy ultimately failed to achieve ignition of the quilt behind the target.

[0057] Example 2

[0058] S1: Weigh 139.3 g of Ti powder, 265.6 g of Zr powder, 526.8 g of Ta powder, and 68.3 g of Ni powder in a molar ratio of 1:1:1:0.4, and place them in a ball mill;

[0059] S2: Add 500g of stainless steel grinding balls according to the ratio of the mass of grinding balls to the total mass of raw material powder (including Ti powder, Zr powder, Ta powder, Ni powder) of 1:2;

[0060] S3: Ball milling for 5 h under inert atmosphere at a speed of 100 rpm to obtain uniform TiZrTaNi 0.4 Mixing powders;

[0061] S4: TiZrTaNi 0.4 The mixed powder is filled into an alumina crucible and vibrated, and then placed in a vacuum sintering furnace for compacting. The sintering temperature is 1300°C, the holding time is 2h, and the low-temperature dense TiZrTaNi is obtained after the furnace is cooled. 0.4 High entropy alloys;

[0062] The low temperature dense TiZrTaNi obtained in Example 2 0.4 The high entropy alloy was tested by SEM observation, X-ray diffraction, quasi-static compression, and gun-fired ignition of quilts. The results are as follows:

[0063] Fig.10 The low temperature dense TiZrTaNi obtained in Example 2 0.4 SEM image of high entropy alloy. There is no obvious hole defect in the alloy cross section, which proves that vacuum sintering at 1300℃ can achieve TiZrTaNi 0.4 Densification of high entropy alloys. TiZrTaNi 0.4 The high entropy alloy is mainly composed of two contrasting phases, namely the light-colored Ta-rich phase and the dark-colored Ni-rich phase. The XRD spectrum confirms that the alloy has two sets of diffraction peaks, which can be determined as BCC phase and Ti(Zr)-Ni by PDF card comparison. x Compound phase; quasi-static compression test results show that TiZrTaNi 0.4The yield strength of the high entropy alloy is 1203MPa. After reaching the elastic deformation limit, plastic deformation continues to occur. The final quasi-static compressive strength reaches 1367MPa and the fracture strain is 7.0%. The gun firing experiment confirms that the low-temperature dense TiZrTaNi obtained in Example 2 0.4 The high-entropy alloy can effectively penetrate the 6mm thick front steel plate at a speed of 800m / s, and at the same time ignite the quilt behind the target. The flames are obvious, showing excellent impact response characteristics.

[0064] Example 3

[0065] S1: Weigh 134.8 g Ti powder, 256.8 g Zr powder, 509.3 g Ta powder, and 99.1 g Ni powder in a molar ratio of 1:1:1:0.6, respectively, and place them in a ball mill;

[0066] S2: Add 500g of stainless steel grinding balls according to the ratio of the mass of grinding balls to the total mass of raw material powder (including Ti powder, Zr powder, Ta powder, Ni powder) of 1:2;

[0067] S3: Ball milling for 5 h under inert atmosphere at a speed of 100 rpm to obtain uniform TiZrTaNi 0.6 Mixing powders;

[0068] S4: TiZrTaNi 0.6 The mixed powder is filled into an alumina crucible and vibrated, and then placed in a vacuum sintering furnace for compacting. The sintering temperature is 1200°C, the holding time is 2h, and the low-temperature dense TiZrTaNi is obtained after the furnace is cooled. 0.6 High entropy alloys;

[0069] The low temperature dense TiZrTaNi obtained in Example 3 0.6 The high entropy alloy was tested by SEM observation, X-ray diffraction, quasi-static compression, and gun-fired ignition of quilts. The results are as follows:

[0070] Fig.11 The low temperature dense TiZrTaNi obtained in Example 3 0.6 SEM image of high entropy alloy. There is no obvious hole defect in the alloy cross section, which proves that vacuum sintering at 1200℃ can achieve TiZrTaNi 0.6 Densification of high entropy alloys. TiZrTaNi 0.6 The high-entropy alloy is mainly composed of three contrast phases, namely the light-colored Ta-rich phase, the light-gray Ni-rich phase and the dark TiZrNi ternary phase. The XRD spectrum confirms that the alloy mainly has two sets of diffraction peaks, which can be determined as the BCC phase and the Ti-Ni compound phase by PDF card comparison. In addition, there are a small number of weak diffraction peaks corresponding to the TiZrNi ternary phase. The quasi-static compression test results show that TiZrTaNi 0.6The yield strength of the high entropy alloy is 1123MPa. After reaching the elastic deformation limit, a small amount of plastic deformation continues to occur. The final quasi-static compressive strength reaches 1209MPa, and the fracture strain is 5.9%. The gun firing experiment confirms that the low-temperature dense TiZrTaNi obtained in Example 3 0.6 The high-entropy alloy can effectively penetrate the 6mm thick front steel plate at a speed of 800m / s, and at the same time ignite the quilt behind the target. The flames are obvious, showing excellent impact response characteristics.

[0071] Example 4

[0072] S1: Weigh 130.4 g Ti powder, 248.6 g Zr powder, 493.1 g Ta powder, and 127.9 g Ni powder in a molar ratio of 1:1:1:0.8, respectively, and place them in a ball mill;

[0073] S2: Add 500g of stainless steel grinding balls according to the ratio of the mass of grinding balls to the total mass of raw material powder (including Ti powder, Zr powder, Ta powder, Ni powder) of 1:2;

[0074] S3: Ball milling for 6 hours under inert atmosphere protection, ball milling speed 80rpm, to obtain uniform TiZrTaNi 0.8 Mixing powders;

[0075] S4: TiZrTaNi 0.8 The mixed powder is filled into an alumina crucible and vibrated, and then placed in a vacuum sintering furnace for compacting. The sintering temperature is 1100°C, the holding time is 3h, and the low-temperature dense TiZrTaNi is obtained after the furnace is cooled. 0.8 High entropy alloys;

[0076] The low temperature dense TiZrTaNi obtained in Example 4 0.8 The high entropy alloy was tested by SEM observation, X-ray diffraction, quasi-static compression, and gun-fired ignition of quilts. The results are as follows:

[0077] Fig.12 The low temperature dense TiZrTaNi obtained in Example 4 0.8 SEM image of high entropy alloy. There is no obvious hole defect in the alloy cross section, which proves that vacuum sintering at 1100℃ can achieve TiZrTaNi 0.8 Densification of high entropy alloys. TiZrTaNi 0.8The cross section of the high entropy alloy shows a recrystallized morphology, indicating that there may be a large amount of self-reaction heat release during the long-term heat preservation process, which promotes the recrystallization process of the alloy. The alloy is mainly composed of three contrast phases, namely, light Ta-rich phase, light gray Ni-rich phase and dark TiZrNi ternary phase; through XRD spectrum analysis, the three phases are BCC phase, Ti-Ni compound phase and TiZrNi ternary phase; quasi-static compression test results show that TiZrTaNi 0.8 The yield strength of the high entropy alloy is 1046MPa. After reaching the elastic deformation limit, a small amount of plastic deformation occurs. The final quasi-static compressive strength reaches 1105MPa, and the fracture strain is 4.1%. The gun firing experiment confirms that the low-temperature dense TiZrTaNi obtained in Example 4 0.8 The high-entropy alloy can effectively penetrate the 6mm thick front steel plate at a speed of 800m / s, and at the same time ignite the quilt behind the target. The flames are obvious, showing excellent impact response characteristics.

Claims

1. A low temperature dense high entropy alloy, characterized in that The molar ratio of the components Ti, Zr, Ta and Ni in the alloy is 1:1:1:0.2-0.

8.

2. A method for preparing a low temperature dense high entropy alloy according to claim 1, characterized in that The following steps are involved: ① Weigh Ti, Zr, Ta and Ni raw material powders according to the designed ratio and mix them evenly in a ball mill; ② Mix the uniform TiZrTaNi x The powder is filled into the crucible and compacted; ③ The compacted TiZrTaNi x The mixed powder is vacuum sintered and cooled in the furnace to obtain a low-temperature dense high-entropy alloy.

3. The preparation method according to claim 2, characterized in that In step ①, the particle size of the Ti powder is 10-60 μm; the purity of the Ti powder is ≥99.95%.

4. The preparation method according to claim 2, characterized in that In step ①, the particle size of Zr powder is 45-74 μm; the purity of Zr powder is ≥99.95%.

5. The preparation method according to claim 2, characterized in that In step ①, the particle size of Ta powder is 30-50 μm; the purity of Ta powder is ≥99.95%.

6. The preparation method according to claim 2, characterized in that In step ①, the particle size of Ni powder is 2.5-10 μm; the purity of Ni powder is ≥99.95%.

7. The preparation method according to claim 2, characterized in that The ball milling conditions in step ① are as follows: rotation speed 80-150 rpm, ball-to-material ratio 1:2-2:1, ball milling time 4-6 h, and inert atmosphere protection.

8. The preparation method according to claim 2, characterized in that The vacuum sintering process parameters in step ③ are: sintering temperature 1100-1300° C., holding time 2-3 h, vacuum degree ≤10 Pa.